Kecenderungan Naiknya Suhu Permukaan Laut dan Resiliensi Karang Setelah Kejadian Pemutihan Karang 2010 dan 2016 di Taman Wisata Perairan (TWP) Pulau Pieh, Padang, Sumatra Barat - Sam Wouthuyzen; Muhammad Abrar; Corry Corvianawatie; Suryo Kusumo; Yogi Yanuar; Darmawan; Yennafri; Abu Salatalohi; Andriyatno Hanif; Syeprianto Permana; et al. (OLDI (Oseanologi dan Limnologi di Indonesia), 2026)
Trend of Sea Surface Temperature Increase and Coral Resilience After Bleaching Events of 2010 and 2016 in The Marine Tourism Park (TWP) of Pieh Island, Padang, West Sumatra. The coral bleaching event has hit almost all of Indonesia’s waters at least 4 times (in the last 34 years), which the last two events (2010 and 2016) have been discussed rather deeply. However, detailed studies in a specific location, such as in Marine Tourism Park (TWP) of Pieh Island, Padang waters, West Sumatra Province that influenced by the water mass of Indian Ocean have not yet been studied. The aim of this paper is to examine the trend of sea surface temperatures (SST)’s increase in the TWP of Pieh Island in 2010 and 2016 coral bleaching, and the coral resilience after the events. In this study, the long-term SST data acquired from the Aqua MODIS satellite images were used intensively. Results show that the highest mean monthly SST called MMM that corals can be tolerated in the TWP of Pieh is 29.6 oC, higher than in all Indonesian waters (29.1 oC).The differences between the anomaly SST and the normal SST (MMM) or called Hot Spot (HS) has exceeded the average MMM in the 2010 bleaching event around 0.4-0.5 oC with its peak in April, and with alert-1 severity (Degree Heating Weeks (DHW) < 8 oC-weeks; which means that the coral has partial bleaching with patchy pattern).In 2016, the HS increased by an average of 0.5 1.0 oC with peaks in January-February and May-June and with the severity of Alert-2 (DHW ≥ 8 oC-weeks, which means corals experienced severe bleaching, over wider areas, and some of corals are died). One year earlier (2015), higher HS with an average value of 0.3-0.8 oC and DHW 4 oC-weeks were also observed. This indicates that coral bleaching events in the TWP of Pieh Island is repeated and occurs for long periods.The trend of increasing SST in this TWP is 0.23oC/decade, lower than in the all Indonesian waters (0.36 oC/decade). This trend shows that coral reefs in Indonesian waters including this TWP have a high resilience to recover themselves from bleaching, since the trend of increasing SST < 1.0 oC/decade of the 11 coral resilience key factors, positive factors that support high coral resilience are low pollution/nutrients, low sedimentation (high water transparency), and low unfriendly of human activities, while the most negative one is the explosion of crown-of-thorns starfish, Acanthaster planci population as well as coral disease.